The relationship between atherogenic index of plasma and major risk factors of cardiovascular disease in obese and non-obese individuals - Sayın, Seher; Kutlu, Ruhuşen; Koçak, Ahmet (The European Research Journal, 2019)
Objectives: Obesity is a health problem with gradually increasing prevalence and directly contribute to the development of cardiovascular disease (CVD). We aimed to investigate the relationship between atherogenic index of plasma (AIP) and major risk factors of CVD in obese and non-obese individuals. Methods: This analytical case-control study was carried out on 501 individuals. Obese patients were included in the case group and normal-overweight individuals were included in the control group. The groups were similar in terms of ages and gender. Detailed medical background of the participants was recorded and antropometric parameters were measured. High-density lipoprotein-cholesterol, low-density lipoprotein-cholesterol, total cholesterol, triglyceride, fasting blood glucose (FBG) and insulin were measured. AIP risk categories were created according to published epidemiological data: AIP < 0.1 is associated with low risk, 0.1-0.24 with moderate risk, and > 0.24 with high risk. Results: There was a statistically significant relationship between obesity, male gender, older age, smoking, insulin resistance, high waist circumference, elevation of the blood pressure, FBG and high CVD risk (p < 0.005). CVD risk in males were 6.254 times more than in females [OR=6.254, 95% CI; (2.287-17.107)], CVD risk in obese was 3.436 times more than in none-obese and CVD risk in individuals with insulin resistance was 5.560-fold increase than individuals without insulin resistance [OR=5.560, 95% CI; (3.069-10.070)] (p < 0.001). Conclusions: Our findings showed that increasing in AIP is associated with obesity and other cardiovascular risk factors. Therefore, AIP can be used as a simple, economic and non invasive marker to identify for CVD risk.